TRANSFORMASI POTENSI PRODUK UNGGULAN DESA TULLENG KECAMATAN LEMBUR KABUPATEN ALOR - Yessy Mata; Robinson Sedama, Denis Thomas Djaha, Loin Hamap, Yunita Ekaria Bain, Helli Pilanti Perangsir, Kain S (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study discusses the transformation of the potential of superior products in Tulleng Village, Lembur District, Alor Regency, which until now have not been optimally utilized as a source of economic improvement for the community. The purpose of this community service journal is to identify the village's superior potential, analyze the obstacles faced, and formulate development strategies that can support community welfare. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the observation indicate that Tulleng Village has several potential superior products, including rice fields, corn, sweet potatoes (cassava), bananas, porang, and forest wood. This potential has added economic value if managed professionally and sustainably. However, there are still obstacles such as a lack of community understanding of business management, low product processing skills, and a lack of innovation. Development efforts can be carried out through increasing human resource capacity, empowering business groups, product innovation, and government support in terms of access to capital and marketing. By implementing these strategies, Tulleng Village's superior products have the potential to be developed into commodities that not only have local value but are also able to compete in the global market.